Development of Adobe Flash Media in Increasing Learning Interest - Dhia Asy Syafa; Pratiwi Pujiastuti; Deri Anggraini (STAI Hubbulwathan Duri, 2021)
This research aims to develop learning media products based on Adobe Flash in Indonesian Language Courses in the Elementary School Teacher Education Study Program. This research was conducted through four main stages: define, design, develop, and disseminate. This study uses a questionnaire as a data collection instrument, adapting quantitative research methods with a quasi-experimental approach (quasi-experimental) at the implementation stage in this study. The data to be obtained in the study were collected through interviews, questionnaires, and product rating scales. This scale collected data at the product validity stage, small group trials, and primary field trials. The results of the development of learning media products using a 4D development model with seven main components. Based on the results of the feasibility validation obtained in the Expert test and the initial field test, the feasibility of the media and material the value obtained is